Vapour phase oxidation of acetophenone to benzoic acid over binary oxides of V and Mo - Chumbhale, Vilas R.; Paradhy, S. A.; Anilkumar, Mettu; Kadam, S. T.; Bokade, Vijay V. (Chemical Engineering Research and Design, 2005)
Test data for catalytic oxidation of acetophenone into benzoic acid performed at bench scale with V2O5-MoO3 catalyst in a continuous downflow metal reactor are presented. The process parameters such as temperature and flow rate influence the product distribution. The P2O5, B2O3 and Na2O when used as dopant on V2O5-MoO3 catalyst showed marked influence on activity and selectivity. An acidic catalyst like V2O5-MoO3-P2O5 favours formation of benzoic acid while a basic catalyst like V2O5-MoO3-Na2O favours formation of benzaldehyde. The addition of Na2O into V2O5-MoO3 binary oxides formed new phases (NaVMoO6 and Na2V2Mo3O15), which increased Arrhenius activation energy from 18.24 to 31.35 kcal mol(-1).
Keywords: acetophenone; activity; benzoic acid; carbon oxides; oxidation of acetophenone; selectivity

Discontinuous two step flow synthesis of m-aminoacetophenone - Tibhe, Jagdish; Sharma, Yachita; Joshi, Ramesh A.; Joshi, Rohini R.; Kulkarni, Amol A. (Green Processing and Synthesis, 2014)
The continuous flow nitration of acetophenone followed by reduction of the meta isomer has been demonstrated using simple tubular reactors. Because of ease of separation of the desired isomer from the first step, both steps are made continuous, but separately. The continuous flow nitration was carried out in a safe manner in a shorter reaction time than the conventional approach. The choice of micromixer was seen to affect the performance of the nitration reaction. The effect of different parameters on the yield of the desired product was studied. The reduction step with sodium sulfide was found to be economical and could be carried out efficiently at 70 degrees C using sodium sulfide in ethanol, using a silicone tube. Both steps were demonstrated for several hours, yielding a sufficiently large quantity (similar to 100 g) of m-aminoacetophenone at lab scale in a single day using simple tubular reactors.
Keywords: acetophenone; continuous flow synthesis; microreactor; nitration; reduction

Review on selective production of acetophenone from oxidation of ethylbenzene over heterogeneous catalysts in a decade - Nandanwar, Sachin U.; Rathod, Simmy; Bansal, Videsha; Bokade, Vijay V. (Catalysis Letters, 2021)
The consumption of acetophenone (AP) is increasing worldwide because of its applications in products such as alcohol, aldehydes, resins, esters, fragrances, and pharmaceuticals. AP is manufactured via several methods like decomposition of cumene hydroperoxide, Hock process, and Friedel-Crafts acylation reaction using homogeneous catalysts with solvent and oxidant. However, it causes several environmental problems that deteriorate the production of AP with these methods. Oxidation of ethylbenzene (EB) is one of the promising methods to synthesize AP in liquid and vapor phases reaction using heterogeneous catalysts, which plays a vital role for selective production of AP. In this review, numerous heterogeneous catalysts are discussed including transition metal nanoparticles, transition metal complexes, and metal free catalysts (carbon nanotubes) used in last 10 years for oxidation of EB. Additionally, catalyst activity along with reaction parameters and its effect, mechanisms, and kinetics study are summarized in this article. The future scope of this reaction is also highlighted. Moreover, this work identifies best catalysts for bulk production of AP with high yield to satisfy global requirement.
Keywords: acetophenone; ethylbenzene; Heterogeneous catalysts; Oxidation reaction; reaction mechanisms